PENENTUAN KELAS KEMAMPUAN LAHAN DAERAH TANGKAPANAIR DANAU TOBA MENGGUNAKAN METODE SCORING - Eko Moriye Simangunsong; Razali Razali; Mukhlis Mukhlis (Universitas Sumatera Utara, 2013)
The research of land capability classification survey is held on the area of water capturing (DTA) of Danau Toba. Land capability classification is fulfilled by using scoring methods based on the land unit in DTA of Danau Toba. The scorring of limitation factor of each land unit is held to obtain land capability class. Here are the limitation factors of each land unit: the depth of efectivity land, texture, drainage, permeability, slope, erotion, flood and surface stone.The research outcome shows that there are totally 36 land units which are divided into 8 land capability classes. Land width of the first class is 26.484.59 ha, the second class is 73.422.64 ha, the third class is 32.912.79 ha, the fourth class is 28.442.06 ha, the fifth class is 21.751.94 ha, the sixth class is 2.749.55 ha, the seventh class is 618.26 ha and the eight class is 30.155.78 ha. Keywords: land capability class, land unit, scorring.